Comparative study of methods for teaching periodic table 'PT made easy' in chemistry subject - Mohd Shotor, Siti Noriah; Sheikh Mohd Ghazali, Sheikh Ahmad Izaddin; Amat, Wilson Alyadrian; Juraizam, Muhammad Haiqal Muistaqim (2022)
Chemistry is one of the most difficult subjects in school because it requires critical thinking and problem solving skills. The subject involves the study of the composition, properties, and reactions of matter at the chemical level. This article will focus on the periodic table, which is a table that organizes the chemical elements according to their atomic number. The periodic table is also known as the periodic chart, which is a chart that visually organizes the elements by their atomic number. The problem with the students that have no basics in chemistry is that they can't understand the periodic table. Understanding this periodic table is particularly important for the subject of chemistry itself. For students who are just learning this subject for the first time, such as STEM C students, will be experiencing difficulty to understand the periodic table. Thus, this study will be focusing on the comparison between memorization techniques through songs and comparing them with conventional method. As a result, from the survey we did, it was found that musical memorization is easier to memorize compared to the usual method.